Clarifying Husserl’s Epoche: Misinterpretations and its Role in Phenomenological Inquiry through Dan Zahavi’s Perspective - Das, Subhajit (PT FORMOSA CENDEKIA GLOBAL, 2025)
Husserl’s concept of epoché is central to phenomenology, allowing for the suspension of presuppositions to examine experience as it is given. It provides a neutral standpoint for exploring consciousness and the structures of experience and being. Dan Zahavi, in Husserl’s Phenomenology, offers a nuanced interpretation of epoché, clarifying its purpose and addressing common misunderstandings particularly the false view that it denies or abandons reality. Zahavi emphasizes that epoché suspends dogmatic attitudes toward reality, not reality itself, enabling a more authentic engagement with how consciousness constitutes meaning. His interpretation deepens the methodological and philosophical significance of Husserl’s thought, particularly in relation to subjectivity, intentionality, and world constitution.